2018
DOI: 10.1016/j.jmig.2017.08.651
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Single-Port Laparoscopic Myomectomy Compared with Conventional Laparoscopic Myomectomy: A Randomized Controlled Study

Abstract: SP-LM is associated with more favorable cosmetic outcomes and better patient satisfaction compared with CLM. There were no differences in operative outcomes and complications between the 2 modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
5
25
0
Order By: Relevance
“…In our study, the mean number of myoma in a single patient was 3.84 ± 2.45, which is comparable to previous studies [18,19,[21][22][23][24][25] , which range from 1-5. However, in one patient in our study, 10 myomas were removed in the same operation, which we believe is the most reported in the literature in a single-port laparoscopic myomectomy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the mean number of myoma in a single patient was 3.84 ± 2.45, which is comparable to previous studies [18,19,[21][22][23][24][25] , which range from 1-5. However, in one patient in our study, 10 myomas were removed in the same operation, which we believe is the most reported in the literature in a single-port laparoscopic myomectomy.…”
Section: Discussionsupporting
confidence: 90%
“…Table 5. Comparison of surgical outcomes with previous published studies [18,19,[21][22][23][24] *Immediately arrive ward after operation; **24 hours later. VAS: visual analogue score…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2 Especially for women who want to retain the uterus and fertility, if surgery is required, uterine myomectomy must be performed without removing the entire uterus. 3 Therefore, the laparoscopic myomectomy under general anesthesia is a preferred option for uterine myoma treatment instead of laparotomy. 4,5 Compared with laparotomy, laparoscopic surgery shows many advantages, such as lower perioperative morbidity, quicker recovery, and shorter hospital stay without reducing efficacy.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Especially for women who want to retain the uterus and fertility, if surgery is required, uterine myomectomy must be performed without removing the entire uterus. 3 Therefore, the laparoscopic myomectomy under general anesthesia is a preferred option for uterine myoma treatment instead of laparotomy. 4 , 5…”
Section: Introductionmentioning
confidence: 99%